2023
DOI: 10.1021/acs.jpclett.3c01206
|View full text |Cite
|
Sign up to set email alerts
|

Cryogenic Absorption and Emission Spectroscopy of the Oxyluciferin Anion In Vacuo

Abstract: Bioluminescence from fireflies, click beetles, and railroad worms ranges in color from green-yellow to orange to red. The keto form of oxyluciferin is considered a key emitter species in the proposed mechanisms to account for color variation. To establish the intrinsic photophysics in the absence of a microenvironment, we present experimental and theoretical gas-phase absorption and emission spectra of the 5,5-dimethyloxyluciferin anion (keto form) at room and cryogenic temperatures as well as lifetime measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…This gives rise to more than a doubling of the Stokes shift from 14 cm À1 to 37 cm À1 . The Stokes shifts measured for the oxazines are similar to those for rhodamine cations (17-25 cm À1 ) 26 but smaller than those for fluorone anions and that for the dimethyl-oxyluciferin anion; in the latter case the shift is an order of magnitude larger (360 cm À1 ) 14 Both absorption and fluorescence spectra of rhodamine cations are, however, much less well-resolved than those of oxazines, which is likely associated with differences in the importance of low frequency modes.…”
Section: Resultsmentioning
confidence: 56%
See 4 more Smart Citations
“…This gives rise to more than a doubling of the Stokes shift from 14 cm À1 to 37 cm À1 . The Stokes shifts measured for the oxazines are similar to those for rhodamine cations (17-25 cm À1 ) 26 but smaller than those for fluorone anions and that for the dimethyl-oxyluciferin anion; in the latter case the shift is an order of magnitude larger (360 cm À1 ) 14 Both absorption and fluorescence spectra of rhodamine cations are, however, much less well-resolved than those of oxazines, which is likely associated with differences in the importance of low frequency modes.…”
Section: Resultsmentioning
confidence: 56%
“…The fluorescence spectrum (blue) exhibits maximum intensity at 565.5 AE 0.5 nm, and the spectrum is significantly broader but still shows appreciable vibrational structure. In our previous work 9,14,25,26 on a range of similar fused three-ring systems (pyronin Y, rhodamines, fluorones) and dimethyl-oxyluciferin, the fluorescence spectra were also broader and more congested than the fluorescence-excitation spectra. We showed that it was caused by an increased effective temperature of the ions due to excess energy deposited by the absorbed laser photon.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations